2017
DOI: 10.1016/j.jecp.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in maternal education and minimal exposure effects on vocabulary in English- and Spanish-learning toddlers

Abstract: The present research follows up on two previous findings: that children with minimal dual language exposure have smaller receptive vocabularies at 16 months and that maternal education is a predictor of vocabulary when the dominant language is English but not when it is Spanish. The present study extends this research to 22-month-olds to assess the developmental effects of minimal exposure and maternal education on direct and parent-report measures of vocabulary size. The effects of minimal exposure on vocabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Similar to the findings of previous work that documented differences in the speech and language outcomes of children of more vs. less educated mothers (De Anda et al 2016;Friend et al 2017;Hammer et al 2012;Hoff et al 2018;Montanari et al 2020;Place and Hoff 2016), we found that children's overall segmental accuracy in English and their production accuracy with English stops, approximants, and English-specific phonemes were positively and moderately correlated with their mothers' levels of American orientation. Likewise, overall English consonant accuracy and accuracy with approximants and with unshared phonemes were also positively and moderately correlated with maternal linear acculturation scores.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to the findings of previous work that documented differences in the speech and language outcomes of children of more vs. less educated mothers (De Anda et al 2016;Friend et al 2017;Hammer et al 2012;Hoff et al 2018;Montanari et al 2020;Place and Hoff 2016), we found that children's overall segmental accuracy in English and their production accuracy with English stops, approximants, and English-specific phonemes were positively and moderately correlated with their mothers' levels of American orientation. Likewise, overall English consonant accuracy and accuracy with approximants and with unshared phonemes were also positively and moderately correlated with maternal linear acculturation scores.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the majority of previous studies have found that maternal level of schooling-measured in terms of the number of years of education attained irrespective of the language-has a different impact on children's English versus Spanish development. Specifically, while research has shown clear links between maternal education and children's English outcomes, mothers' school attainment has not been found to be related to Spanish outcomes, at least in De Anda et al (2016), Friend et al (2017), and Place and Hoff (2016). By controlling the language in which mothers received their education, Hoff et al (2018) found that maternal school attainment in English was significantly related to children's English but not to Spanish vocabulary between 30 and 60 months, and maternal level of education in Spanish predicted children's Spanish but not English lexical skills between the same ages.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, multiple studies have suggested that maternal education level contributes to positive parent-infant interaction by influencing parenting styles and timing of paternal investment. [28,29]. One study observing 139 Chinese infants aged 12-24 months found that highly educated mothers were more likely to utilize guiding behaviors, and they developed higher levels of intimacy with their infants compared to less-educated mothers [30].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, DeAnda et al (2016) compared monolingual l6‐month‐old infants with 100% exposure to English to bilingual learners with 80% exposure to English. The two groups differed in vocabulary size estimates, a gap which later narrowed at 22 months (Friend et al, 2017). Therefore, it remains unclear whether language exposure thresholds are useful in defining bilingualism.…”
Section: An Overview Of Language Use In Singaporementioning
confidence: 99%